2018
DOI: 10.1038/s41598-018-31332-6
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Cultures of NSCLC cells grown at the Air-Liquid Interface allow the efficacy testing of inhaled anti-cancer drugs

Abstract: Evidence supports the advantages of inhalation over other drug-administration routes in the treatment of lung diseases, including cancer. Although data obtained from animal models and conventional in vitro cultures are informative, testing the efficacy of inhaled chemotherapeutic agents requires human-relevant preclinical tools. Such tools are currently unavailable. Here, we developed and characterized in vitro models for the efficacy testing of inhaled chemotherapeutic agents against non-small-cell lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 93 publications
5
53
0
Order By: Relevance
“…Due to limited current data, future study of targeting common cancer initiating genes with non-coding RNAs using organoid models could serve as promising indicators for clinical therapeutic response and tumorigenesis. A form of in vitro modeling includes air-liquid interface models, which attempt to mimic the microenvironment of the lungs [301]. Movia et al utilized these multilayered cultures to test response chemotherapy administered through inhalation and they found that these models demonstrated high chemoresistance [301].…”
Section: Pre-clinical Models For Human Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Due to limited current data, future study of targeting common cancer initiating genes with non-coding RNAs using organoid models could serve as promising indicators for clinical therapeutic response and tumorigenesis. A form of in vitro modeling includes air-liquid interface models, which attempt to mimic the microenvironment of the lungs [301]. Movia et al utilized these multilayered cultures to test response chemotherapy administered through inhalation and they found that these models demonstrated high chemoresistance [301].…”
Section: Pre-clinical Models For Human Lung Cancermentioning
confidence: 99%
“…A form of in vitro modeling includes air-liquid interface models, which attempt to mimic the microenvironment of the lungs [301]. Movia et al utilized these multilayered cultures to test response chemotherapy administered through inhalation and they found that these models demonstrated high chemoresistance [301]. Further study of therapeutic efficacy using miRNAs by mimicking the lung microenvironment with air-liquid interface models could serve as promising future study.…”
Section: Pre-clinical Models For Human Lung Cancermentioning
confidence: 99%
“…Also, they can replicate some of the key features that need to be kept into account when developing an inhalation therapy, namely (i) the constitution and thickness of the pulmonary lining fluid [67] and (ii) mucociliary clearance [60][61][62]. For example, ALI cultures have been used to model the effects of smoke exposure on epithelial cells [104] and the authors have created a complex, diseased ALI culture model capable of reproducing the chemoresistance mechanisms observed in patients affected by non-small-cell lung cancer [105,106]. Also, culturing human airway epithelial cells isolated from patients, makes it possible to conduct patient-specific research and drug-screening, for example in cystic fibrosis, asthma and COPD [107][108][109][110].…”
Section: Ali Culturesmentioning
confidence: 99%
“…Despite these limitations, primary respiratory epithelial ALI culture models have been used to recapitulate in vivo airway epithelia as a biologically relevant in vitro drug screening platform (Ong et al, 2016). ALI culture systems have been heavily reviewed in the literature and have delivered highly impactful research outcomes (Movia et al, 2018;Upadhyay and Palmberg, 2018) however, the use of in vitro ALI models to determine toxicity, delivery and efficacy of inhaled therapeutics requires greater physiological and anatomical relevance. Specifically, in vitro respiratory models that implement breathing mechanics, aerosol deposition, and the co-culture of different cell types allow greater mechanistic and efficacious insights of novel inhalable therapeutic compounds.…”
Section: Progress and Limitations Of In Vitro Air-liquid Interface Momentioning
confidence: 99%